Directions in logistics coordination in cities and metropolitan areas: economic-mathematical vision - Averkyna, Maryna F. (Management and Administration Journal, 2019)
The article is devoted to the formation of an economic-mathematical model of logistic coordination flows in cities and metropolitan areas. The author reveals the essence, objectives and priorities of the transport, financial and information logistics coordination. The model of logistic coordination of transport flows is proposed. The model of logistics coordination of financial flows in cities and metropolitan areas, based on the Black-Scholes model, is proposed. The model of logistics coordination of information flows is proposed.